十八岁出门远行 “Partir lejos de casa a los dieciocho” de Yu Hua余华 - Rodríguez Durán, Pablo (2015)
“On the Road at Eighteen” is a short-story that reflects a literary movement born due to a disenchantment with the artistic expressions of Socialist Realism. In the indeterminate language style of Yu Hua, it can glimpse the same uncertainty in the emotions of a young traveler, experiencing the transition from childhood to adult life. A shattered China as the main stage and a new approach to the individual, in literature and in life.